The Impact of Microbiota-Gut-Brain Axis on Diabetic Cognition Impairment - Xu, Youhua; Zhou, Hua; Zhu, Quan (Frontiers in Aging Neuroscience, 2017)
Among the senior citizens, there is a growing tendency to get diabetic encephalopathy (DE), and it has become a major threat which can seriously affect the public health. DE is featured by progressive cognitive dysfunction. The previous studies during the decade have presented the importance of the risk factors such as oxidative stress and inflammation on the development of cognitive impairment. With the recognition of the two-way communication between gut and brain, recent investigation suggests that “microbiota-gut-brain axis” also plays a pivotal role in modulating both cognition function and endocrine stability. This review aims to systemically elucidate the underlying impact of diabetes on cognitive impairment.